Confiança nas Instituições e Valores Culturais : Estudo Internacional Comparado entre Angola, Cabo Verde, Moçambique e Portugal - Finuras, Paulo (2014)
The present study shows the results of an international comparative research carried out in four Portuguese-speaking countries: Angola, Cape Verde, Mozambique and Portugal. The purpose is, firstly, to find these countries cultural profile according to Hofstede/ Minkov dimensions as well as to measure the citizens` level of trust in institutions and, secondly, to analyze the relation between cultural values and level of trust. A bibliographic and theoretical review has been made on the main theoretical references about trust as far as its multiple forms and dimensions are concerned. Then, a scale of confidence in institutions has been drawn. An extensive analysis has been carried out, using qualitative and quantitative methods, including factorial analysis and simple linear regression. The results provide relevant information on what makes the four target countries very alike and on what differentiates them the most. In Portugal, a tendency towards a growing trust in institutions of public offering has been registered, whereas in the African countries, citizens tend to trust institutions of private offering more. All the institutions connected with the judicial and political sphere of society have been negatively qualified by the respondents in all countries, in a relatively similar way.